THE EFFECTS OF EMPLOYEES WORK STRESS AND WORK DISCIPLINE ON THE PERFORMANCE OF EMPLOYEES MEDIATED BY ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) - Rama Setiaji, Pratama; Johannes Lo, Singmin (Dinasti Publisher, 2020)
The purpose of this study is to understand and explain the effects of work stress and work discipline on employees performance mediated by Organizational Citizenship Behaviour and its implications for the Employees of PT Bank “X”. (Persero), Tbk. The research method used was quantitative approach, where the population in this study was 150 employees of PT Bank “X”. (Persero) Tbk. The sample selection technique was done by taking non-probability sampling of 109 respondents. Questionnaire survey instrument data collection technique was used and was submitted to Employees of PT Bank “X” (Persero). Tbk. The data of this study, which was analyzed using the Structural Equation model (SEM) with SmartPLS 3.2.8 software programs, revealed that work stress, Work Discipline and Organizational Citizenship Behavior affect employee performance, both partially and simultaneously.